Ilíada, um terreno de glória (Minerva, 2019)
An epic poem, expressed as a masculine and military celebration, as the Iliad is, must put the idea of glory in the level of principles that bread the warrior’s soul, that encourage him in the effort to save his own and his companions’ lives. Then glory is an ideal that needs effort and solidarity, which distinguishes the best men as superior by their arete and touched by divine help, and that represents for those who obtain it the greatest compensation; by glory, the human being obtains the respect of his contemporaries, and at the same time he escapes from his ephemerous nature and insignificancy to win a bright and paradigmatic immortality. This is the supreme distinction admitted by the Iliad for the excellence of its heroes.Impressive are the words that express it within several contexts: κῦδος, εὖχος y κλὲος form a particularly suggestive vocabulary. Even if sometimes some uncertainty or superposition of sense makes difficult to distinguish between them, it is certain that a different application exists.
Keywords: κῦδος; εὖχος; κλὲος; αἰδώς; φιλία; code of honor